Kekuatan Pembuktian Penjaminan Utang Piutang Melalui Perjanjian Pengikatan Jual Beli - Amara Ayu Maharani; Sri Laksmi Anindita (UNES Law Review, 2024)
Acquiring land rights can be accomplished through various legal acts, one of which involves buying and selling. This research aims to examine the efficacy of guaranteeing debts and receivables through a binding sale and purchase agreement for both debt providers and recipients, as well as to analyze the legal protection afforded to them through such agreements. The research utilizes a normative legal research approach, employing both statutory research and a conceptual framework, and relies on secondary data sources such as statutory regulations, books, and scientific journals. The results of this research indicate that the strength of proof of guaranteeing debts and receivables through a binding sale and purchase agreement for the debtor and debt recipient is invalid and cannot serve as the basis for transferring land rights, except by a PPAT deed or auction. Furthermore, legal protection for guaranteeing debts and receivables cannot be obtained through a valid sale and purchase agreement for the debt provider and the debt recipient. Appropriately, debt and receivable agreements should be guaranteed using mortgage rights.